2016
DOI: 10.1002/jso.24319
|View full text |Cite
|
Sign up to set email alerts
|

Activating KRAS mutation is prognostic only among patients who receive preoperative chemotherapy before resection of colorectal liver metastases

Abstract: KRAS mutation status was an independent predictor of OS among patients undergoing liver resection of CRLM. However, after stratifying by receipt of preoperative chemotherapy, KRAS was informative relative to prognosis only among patients who received preoperative chemotherapy. J. Surg. Oncol. 2016;114:361-367. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Only three previous prediction models included RAS and BRAF mutation status 13–15 , potentially owing to the low prevalence of BRAF mutations in patients with local treatment of CRLMs (approximately 2 per cent) 13 . In contrast to previous studies 28 , 43 , there was no interaction between neoadjuvant treatment status and RAS mutational status here.…”
Section: Discussioncontrasting
confidence: 99%
“…Only three previous prediction models included RAS and BRAF mutation status 13–15 , potentially owing to the low prevalence of BRAF mutations in patients with local treatment of CRLMs (approximately 2 per cent) 13 . In contrast to previous studies 28 , 43 , there was no interaction between neoadjuvant treatment status and RAS mutational status here.…”
Section: Discussioncontrasting
confidence: 99%
“…As such, the practical clinical implications of BRAF mutational status should be further explored. For example, it has been demonstrated that the presence of BRAF mutations in metastatic CRC predicts lack of response to anti-EGFR agent treatment similarly to what occurs in the presence of KRAS pathway mutations (35)(36)(37). Nonetheless, no specific therapy for this patient subgroup is currently in widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…35 KRAS was reported to be informative for prognosis only among patients who received preoperative chemotherapy and not for patients undergone upfront surgery. 36 Thus this is the first report of a significant correlation between KRAS mutant status, CXCR4 and prognosis in CRLM.…”
Section: Discussionmentioning
confidence: 64%